Implementation Of Government Policies In Elimination Of Women Trafficking In North Sulawesi - Tasik, Femmy C.M. (Asia Pacific Journal of Management and Education (APJME), 2019)
The aim of study is to explore the problems related to the implementation of government policies in elimination of women trafficking, especially the role of local governments in implementing national policies for the elimination of women trafficking from executors in the regions. This is to achieve the target of the implementation of what kind is to encourage the elimination of women trafficking and what role of local government is needed so that the national policy of eliminating women trafficking can run well and be able to eradicate women trafficking, so as to provide recommendations for the North Sulawesi provincial government in implementing policy of eliminating women trafficking. The method used in this study is a qualitative descriptive method. The data sources used are primary data sources and secondary data relating to empirical situations and conditions. The implementation of national policies for the elimination of women trafficking in North Sulawesi, both those found in the field, and those analyzed with secondary data, while data collection techniques are observation and in-depth interviews. From the findings of the field, it was found that the implementation of national policies for eliminating human trafficking more specifically for women in North Sulawesi has not been carried out properly and the local government in implementing national policies has not played properly according to what is mandated in the national policy on the elimination of human trafficking. This is because the regional leadership does not care about women and has not been able to integrate the three elements of EVR (Environmental, Values, and Resources).